The Influence of Cinematherapy Against Academic Anxiety in Students - Rubi Rimonda; Siti Zahra Bulantika; Hammi Latifah; Iswatun Khasanah (Jurnal Inspirasi Pendidikan, 2020)
Students with high academic anxiety can cause a decrease in learning motivation. This situation will damage the learning achievement achieved by students. The purpose of this study was to look at the effect of cinematherapy on reducing student academic anxiety. This study uses a one-group pretest-posttest design experimental design. A total of 7 students in SMP Metro 1 were the subjects in this study. Subject selection uses a purposive sampling technique based on high academic anxiety criteria from the results of the academic anxiety scale score. The data analysis technique used is the Wilcoxon test. Statistical test results show that there is an effect of cinematherapy on the decrease in students' academic anxiety. The findings of this study prove that cinema is effective in reducing student academic anxiety at SMPN 1 in the city of Metro, Lampung.